Structure-Activity Relationships of Pentacyclic Triterpenoids as Potent and Selective Inhibitors against Human Carboxylesterase 1 - Zou, Li-Wei; Dou, Tong-Yi; Wang, Ping; Lei, Wei; Weng, Zi-Miao; Hou, Jie; Wang, Dan-Dan; Fan, Yi-Ming; Zhang, Wei-Dong; Ge, Guang-Bo; Yang, Ling (Frontiers in Pharmacology, 2017)
Human carboxylesterase 1 (hCE1), one of the most important serine hydrolases distributed in liver and adipocytes, plays key roles in endobiotic homeostasis and xenobiotic metabolism. This study aimed to find potent and selective inhibitors against hCE1 from phytochemicals and their derivatives. To this end, a series of natural triterpenoids were collected and their inhibitory effects against human carboxylesterases (hCEs) were assayed using D-Luciferin methyl ester (DME) and 6,8-dichloro-9,9-dimethyl-7-oxo-7,9-dihydroacridin-2-yl benzoate (DDAB) as specific optical substrate for hCE1, and hCE2, respectively. Following screening of a series of natural triterpenoids, oleanolic acid (OA), and ursolic acid (UA) were found with strong inhibitory effects on hCE1 and relative high selectivity over hCE2. In order to get the highly selective and potent inhibitors of hCE1, a series of OA and UA derivatives were synthesized from OA and UA by chemical modifications including oxidation, reduction, esterification, and amidation. The inhibitory effects of these derivatives on hCEs were assayed and the structure-activity relationships of tested triterpenoids as hCE1 inhibitors were carefully investigated. The results demonstrated that the carbonyl group at the C-28 site is essential for hCE1 inhibition, the modifications of OA or UA at this site including esters, amides and alcohols are unbeneficial for hCE1 inhibition. In contrast, the structural modifications on OA and UA at other sites, such as converting the C-3 hydroxy group to 3-O-β-carboxypropionyl (compounds 20 and 22), led to a dramatically increase of the inhibitory effects against hCE1 and very high selectivity over hCE2. 3D-QSAR analysis of all tested triterpenoids including OA and UA derivatives provide new insights into the fine relationships linking between the inhibitory effects on hCE1 and the steric-electrostatic properties of triterpenoids. Furthermore, both inhibition kinetic analyses and docking simulations demonstrated that compound 22 was a potent competitive inhibitor against hCE1-mediated DME hydrolysis. All these findings are very helpful for medicinal chemists to design and develop highly selective and more potent hCE1 inhibitors for biomedical applications.